Rancang Bangun Sistem Cerdas Pendeteksi Kerusakan Mesin Pada Sepeda Motor 4 Tak - Aziz, Firman; Wungo, Supriyadi La; jeffry, Jeffry (Universitas Pancasakti, 2024)
The influence of using computer technology in solving a problem is very large, for example in determining motor damage. In this case, it is devoted to 4-stroke motorcycle vehicles. Currently, the average motorcyclist does not know about the symptoms or signs of damage to their vehicle, so motorists ignore these symptoms and consider these symptoms to be trivial problems, which will not cause damage to their motorcycles. Motorists will be aware of these symptoms after they can no longer use their vehicles. This research proposes to design an intelligent system that can help motorized vehicle drivers to find out earlier about symptoms or signs of damage to their vehicles and take appropriate action before more serious damage occurs to their vehicles. The results obtained are that an intelligent system can detect damage to a 4-stroke motor quickly and can facilitate the provision of solutions and the diagnostic process without a 4-stroke motor expert